ANALISIS PENGARUH DESAIN KEMASAN PRODUK DAN KREATIVITAS IKLAN TERHADAP CITRA MEREK PADA KONSUMEN PRODUK MEREK ULTRAMILK (Studi Pada Mahasiswa Fakultas Ekonomika dan Bisnis Unisbank Semarang) - Damayanti N.M, 10.05.51.0059 (Students Journal of Economic and Management, 2014)
This research is the study of the design of the product packaging and advertising creativity to the brand image . Ultramilk is one brand of milk in a box that has been widely recognized by the Indonesian community among both the young and the older . Ultramilk itself has long been a market leader for dairy products in the packaging box in Indonesia . With the aim of analyzing the effect of design variables product packaging and advertising creativity to the brand image. The sample used in this study were 100 respondents with sampling sampelAccidental retrieval techniques , namely sampling is done by every student who by chance met with researchers can be sampled if it is deemed that the person who happened to be found suitable as a source . The data used is primary data and secondary data analysis used include test validity , reliability test , the coefficient of determination , F-test and multiple linear regression to test the hypothesis. Test results of determination unknown variable product packaging design and advertising creativity can explain the variation of 87.2 % to the brand image while the remainingaffected by other variables that were not analyzed in the study.Variabel product packaging design and advertising creativity collectively same effect positive and significant impact on brand image. Data analysis and hypothesis testing showed that the partial product packaging design variables ( X1 ) and a significant positive effect on brand image ( Y ) , advertising creativity variables ( X2 ) is not positive and significant effect on the image of the brand ( Y ) . Keywords : Product Packaging Design , Creativity Advertising and Brand Image